2019
DOI: 10.1080/0144929x.2019.1655095
|View full text |Cite
|
Sign up to set email alerts
|

Compliant activity rather than difficulty accelerates thought probe responsiveness and inhibits deliberate mind wandering

Abstract: Introduction: Mind wandering is a cognitive state that leads to diminished performance and error risk. A controversy over whether easier or more difficult tasks enhance mind wandering has led to mind wandering being proposed as two different states: deliberate and spontaneous. We hypothesise that forced engagement may inhibit non-instrumental activities including deliberate mind wandering. Methods: Twenty-eight seated, healthy participants (age range 19-35, 9 male) interacted with two pairs of stimuli, each pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 24 publications
3
16
0
Order By: Relevance
“…Intentional TUTs were selectively limited during the changing-target SART, consistent with the findings of Subhani et al (2019). This indicates that decreasing the repetitiveness of a task can inhibit intentional TUT.…”
Section: Methodssupporting
confidence: 81%
See 4 more Smart Citations
“…Intentional TUTs were selectively limited during the changing-target SART, consistent with the findings of Subhani et al (2019). This indicates that decreasing the repetitiveness of a task can inhibit intentional TUT.…”
Section: Methodssupporting
confidence: 81%
“…Prior work suggests that people may mind wander during a sustained attention task is because it is monotonous and understimulating (e.g., the mindlessness hypothesis, Thomson et al, 2015). Consistent with this, Subhani et al (2019) observed that increases in compliant activity reduce intentional, but not unintentional TUTs. As such modifying the SART to include more instructional changes which participants need to attend to may also decrease intentional TUTs relative to the standard SART.…”
Section: Methodssupporting
confidence: 64%
See 3 more Smart Citations